Issues on supply and demand for environmental accounting information - Even Fallan (Copenhagen Business School (CBS), 2013)
Environmental accounting information (environmental disclosure) is the main topic of this dissertation. It started out as sporadic disclosure in company staff newspapers, press releases etc., and developed in the 1970s to become more often incorporated in annual reports for US and Northern- and Central European companies (Lessem, 1979). Since then, environmental disclosure has become common in both annual reports and on corporate web sites. All companies listed on Oslo Stock Exchange (OSE) disclosed environmental information in their annual reports as from year 2000 (Fallan, 2007). “The concept “environmental” in this context refers to those disclosures where an organizational process or a production process may have impact on the natural environment” (Fallan and Fallan, 2007). In the four papers of this thesis, the term environmental disclosure refers to companies' self-reported environmental information in media intended for widespread distribution (annual reports, separate environmental reports, web sites, press releases etc.). In addition to publicly available corporate environmental disclosure, environmental information is also supplied as private information by the company itself (private corporate disclosure – e.g. when a company have meetings with one stakeholder to provide or discuss information); publicly available information about the company (and its surroundings) supplied by others than the company itself (public noncorporate information – e.g. news media coverage, research reports, and public databases); and private non-corporate information (e.g. use of independent experts to take water or soil samples and satellite monitoring of land or water). However, the three latter types of environmental information are out of scope of this thesis.
hdl:10398/8856
Keywords: 650